2017
DOI: 10.18203/2349-3291.ijcp20173802
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalance of hepatitis-c infection in multi-transfused thalassemic children: study from a West Indian tertiary care center

Abstract: Background: To study the prevalence of hepatitis-C virus infection in multi-transfused thalassemic children and to correlate these patients with age, number of transfusion, serum ferritin levels and transaminases levels.Methods: This study was conducted in the Department of Pediatrics of a Teaching Institute of Rajasthan. It was a hospital based cross sectional study, conducted over a period of 12 months (April 2016- March 2017). Blood sample for Ant-HCV antibody detection was taken at time of follow-up visit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…When compared to statistics available through peer-reviewed studies from India,[ 15 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] incidence of HIV-1, HBV and HCV in our thalassemia cohort was on the higher side [ Table 7 ]. Most recent reports from our country document the high prevalence of these TTIs due to the use of molecular tests in addition to serological tests like in our study [ Table 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to statistics available through peer-reviewed studies from India,[ 15 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] incidence of HIV-1, HBV and HCV in our thalassemia cohort was on the higher side [ Table 7 ]. Most recent reports from our country document the high prevalence of these TTIs due to the use of molecular tests in addition to serological tests like in our study [ Table 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chakraborty A (2015)[ 25 ] found the age group of less than 15 years to be the most affected. Another study by Agrawal S[ 26 ] found maximum positive cases of hepatitis C among the 12–18 year age group followed by the 9–12 year age group and these were predominantly found among thalassemia patients who had multiple blood transfusions. Contrarily, Supriya L,[ 24 ] in their study, conducted at Manipur observed maximum hepatitis C cases among the 41–50 year age group in males and 31–40 year age group in females.…”
Section: Discussionmentioning
confidence: 99%